A practical theological investigation into the involvement of the Dutch Reformed family of churches with prisoners incarcerated in correctional centers in the Grootvlei management area in the Free State Province - Mohokare, Sesheme Meshack (University of the Free State, 2018)
Abstract not included
Dissertation (M.Th. (Practical Theology))--University of the Free State, 2018
Keywords: Correctional Services Act; Religious denominations; Inmates; Dutch Reformed Church; Grootvlei management; Prison management; Prison ministry